2009
DOI: 10.1172/jci33877
|View full text |Cite
|
Sign up to set email alerts
|

Fulvene-5 potently inhibits NADPH oxidase 4 and blocks the growth of endothelial tumors in mice

Abstract: Hemangiomas are the most common type of tumor in infants. As they are endothelial cell-derived neoplasias, their growth can be regulated by the autocrine-acting Tie2 ligand angiopoietin 2 (Ang2). Using an experimental model of human hemangiomas, in which polyoma middle T-transformed brain endothelial (bEnd) cells are grafted subcutaneously into nude mice, we compared hemangioma growth originating from bEnd cells derived from wild-type, Ang2 +/-, and Ang2 -/-mice. Surprisingly, Ang2-deficient bEnd cells formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
103
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 29 publications
(32 reference statements)
8
103
1
1
Order By: Relevance
“…3 and 5A and Table 1). Fulvene-5 inhibits NOX4 activity to 40% at 5 M in cells (30). In our treatments, we found that fulvene-5 at 10 M starting before 24 hpf significantly abolished NOX4-induced ROS production and arrhythmic phenotype (Figs.…”
Section: Role Of Nox4-derived Ros In Mediating Cardiac Arrhythmia In supporting
confidence: 57%
“…3 and 5A and Table 1). Fulvene-5 inhibits NOX4 activity to 40% at 5 M in cells (30). In our treatments, we found that fulvene-5 at 10 M starting before 24 hpf significantly abolished NOX4-induced ROS production and arrhythmic phenotype (Figs.…”
Section: Role Of Nox4-derived Ros In Mediating Cardiac Arrhythmia In supporting
confidence: 57%
“…ATM-deficient mice fed with antioxidants lived longer, exhibited a reduced incidence of lymphoma and showed mitigated loss of hematopoietic stem cells compared with controls (15,16). We show here that Atm-null mice also exhibit a reduced incidence of lymphoma when given fulvene-5, a known inhibitor of NOX4 (17). Thus, down-regulation of NOX4 ameliorates the detrimental effects of ATM loss in both human cells and in mice.…”
mentioning
confidence: 61%
“…This PlGF-induced vascular remodeling effect resembles activation of the Dll-4-Notch signaling pathways, which define the arteriole identity and restrict vascular sprouting (40,(42)(43)(44)(45)53). Consequently, inhibition of Notch ligands and receptors resulted in generation of a disorganized tumor vasculature that remain poorly perfused and functionally non-productive 40,[42][43][44]54).…”
Section: Discussionmentioning
confidence: 99%